Practical aspects of implementing tight glucose control in the ICU. - Vogelzang M; Ligtenberg JJM (Current Opinion in Clinical Nutrition & Metabolic Care, 2007)
PURPOSE OF REVIEW: The outcomes of intervention studies implementing intensive insulin therapy aimed at tight glucose control (TGC) are yet not conclusive. There is concern about an increasing incidence of hypoglycemic episodes. Normoglycemia is not easy to obtain in a 'real-life' ICU setting. To facilitate the implementation of TGC, we review its practical aspects. RECENT FINDINGS: Point-of-care blood gas/glucose analyzers currently present the best trade-off between accuracy and speed. A nurse-driven dynamic scale protocol leads to the most efficacious and safe implementation of TGC. Paper protocols have been published and computerized protocols are a new development. Closed-loop systems are not yet available for clinical use. SUMMARY: Clinicians should take care in selecting both the patient group and target blood glucose level. As long as doubts remain about the potential benefits, it is important to perform TGC in a safe way. This can be done with a nurse-driven protocol, using arterial blood samples measured on a point-of-care blood gas analyzer. Insulin administration should be continuous, and guided by a dynamic scale protocol either on paper or on the computer. Periodical monitoring of performance and incremental modification of the protocol leads to best results.